Occurrence of disinfection by-products in swimming pools and the estimated resulting cytotoxicity - Carter, Rhys A.A.; Allard, Sébastien; Croué, Jean-Philippe; Joll, Cynthia A. (The Science of the total environment, 2019)
Swimming pools are disinfected to protect against the risk of microbial disease, however, the formation of disinfection by-products (DBPs) is an unwanted consequence. While many studies have reported the occurrence of commonly investigated DBPs (trihalomethanes and haloacetic acids) in pools, few studies have investigated emerging DBP classes, such as the haloketones or haloacetaldehydes, and the nitrogenous haloacetamides, halonitromethanes, haloacetonitriles and N-nitrosamines. This study investigated the occurrence of sixty four DBPs from the eight aforementioned DBP classes in pools employing different treatment methods. Approximately 70% of the DBPs were detected in at least one of the pools, with most concentrations being equal to or greater than those previously reported. Chloral hydrate (trichloroacetaldehyde) was one of many DBPs detected in all chlorinated waters (202 to 1313 μg/L), and, on a molar basis, was the predominant DBP. Several other DBPs, namely chloroacetic acid, dichloroacetic acid, trichloroacetic acid, dichloroacetamide, dibromoacetamide, dibromochloroacetamide and trichloroacetamide, and many of the N-nitrosamines, were measured at concentrations greater than previously reported: up to 200 to 479 μg/L for the haloacetic acids, 56 to 736 μg/L for the haloacetamides and up to 1093 ng/L for some N-nitrosamines. The higher disinfectant residuals required to be employed in Australian pools, and poor pool management (e.g. of chlorine residual and pH) are likely factors contributing to these relatively high DBP concentrations. Where possible, the cytotoxicity values of the investigated DBPs were evaluated, with chloral hydrate representing over 90% of the total chronic cytotoxicity despite only representing up to 64% of the total molar DBP concentration. This study is the first report of bromodichloroacetaldehyde and bromochloroacetaldehyde in pools and is the first investigation of N-nitrosamines in a brominated pool. Furthermore, this work aids in understanding DBPs in both chlorine and bromine treated pools, the latter being the subject of only limited previous studies. [Display omitted] •64 disinfection by-products (DBPs) investigated in Australian pools•First report of bromochloroacetaldehyde and bromodichloroacetaldehyde in pools•First investigation of N-nitrosamines in a brominated pool•Up to 64% of the total molar DBP concentration consisted of chloral hydrate.•Over 90% of the total calculated chronic cytotoxicity was due to chloral hydrate.